2015
DOI: 10.2134/agronj14.0415
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Cover Cropping Affect Crop Yields and Soil Carbon in the San Joaquin Valley, California

Abstract: Rising costs and air quality regulations have created interest in California's San Joaquin Valley (SJV) in production systems that reduce tillage operations and soil disturbance. From 1999 to 2009, we evaluated conventional (CT) and reduced tillage (RT) systems for a cotton (Gossypium hirsutum L.)/tomato (Solanum lycopersicon Mill.) rotation with (CC) and without (NO) cover crops in a Panoche clay loam soil (fine‐loamy, mixed, superactive, thermic Typic Haplocambid) in Five Points, CA, in terms of yield, soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 19 publications
3
51
0
Order By: Relevance
“…The NT systems had more surface residue than the ST systems while the plots with cover crops had more residue than the plots without cover crops (97% for the NTCC, 71% for the NTNO, 27% for the STCC, and 4% for the STNO). These residue levels were similar to previous determinations made in 2004 and 2009 (Mitchell et al, 2015).…”
Section: Useful Conversionssupporting
confidence: 91%
See 1 more Smart Citation
“…The NT systems had more surface residue than the ST systems while the plots with cover crops had more residue than the plots without cover crops (97% for the NTCC, 71% for the NTNO, 27% for the STCC, and 4% for the STNO). These residue levels were similar to previous determinations made in 2004 and 2009 (Mitchell et al, 2015).…”
Section: Useful Conversionssupporting
confidence: 91%
“…Each treatment combination (NTNO, NTCC, STNO, STCC) was replicated four times in a randomized complete block in 29.9‐ft by 270‐ft plots consisting of six beds each. Standard tillage consisted of conventional intercrop tillage operations of residue shredding, multiple diskings to incorporate residues, subsoiling to a depth of about 18 inches, additional disking to break up soil clods, shaping of beds, and power incorporation of the surface soil using a cultimulcher (Mitchell et al, 2015). The only soil disturbance in the NT systems occurred during seeding.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…UC research on the effects of no-till agriculture in cotton and processing tomatoes has found that sustained management of no-till practices can achieve yields comparable to standard tillage (Mitchell, Klonsky et al 2012;Mitchell et al 2015) and can reduce seed banks of weeds (Shrestha et al 2008). Benefits of this method include lower labor costs (Mitchell, Klonsky et al 2012;Mitchell, Singh 2012), reduced particulate matter emissions (Baker et al 2005) and less evaporative water loss (Mitchell, Singh et al 2012), as well as increased soil carbon (Veenstra et al 2007).…”
Section: Tillagementioning
confidence: 99%
“…Similar to many studies (Winnige et al, 1998;Raper, 2002;López et al, 2003;Hänsel et al, 2009;Walther, 2009;Mitchell et al, 2015), the line transect method was chosen to determine the soil coverage. In these experiments, the line length and number of measuring points were adapted to the 3 m working width of the cultivator.…”
Section: Determination Of the Surface Residue Coveragementioning
confidence: 99%